Pengenalan Konsep Manajemen “Pemasaran Online” untuk Meningkatkan Penjualan pada Green Garden Ramayana Resto and Lounge" - Yuliyani; Suharto; Sudarsi (Jurnal Abdimas Pariwisata, 2023)
The implementation of this Community Activity is to introduce concepts and provide direct training related to online marketing management as a strategy to increase sales at Green Garden Ramayan Resto Lounge which is one of the culinary business actors in Yogyakarta. The method used in this activity is to provide material related to online marketing and the practice of directly uploading content or products Green Garden Ramayan Resto Lounge's social media. The results of this activity were that participants had a theoretical understanding of the concept of online marketing management, and participants were also successful in uploading content or products Green Garden Ramayan Resto Lounge's social media.